Evaluation of certain feed resources for carbohydrate and protein fractions and in situ digestion characteristics - SINGH, K K; DAS, M M; SAMANTA, A K; KUNDU, S S; SHARMA, S D (The Indian Journal of Animal Sciences, 2014)
Locally available different feed and forages were evaluated for carbohydrate and protein fractions and digestion characteristics. CP content was similar in non-leguminous forages and higher values were observed in Leucaenaleucocephala leaf (LLM), urd bhnosa and groundnut haulm. Starch content was lower in urd bhoosa (4.70%) and washigher in LLM (25.85%), barley grain (46.35%) and both the concentrate mixtures A (38.61 %) and B (36.52%). Amongdifferent roughages, unavailable fibre fraction C was minimum in LLM (13.05%) and maximum in groundnut haulm (28.35%). NPN% of CP was higher in LLM (22.49%). Intermediately degradable fraction of protein (82) were similar in C.ciliaris (42.92%), LLM (43.39), mixed grass (39.61%) and higher in urd bhoosa (53.66%). Fraction C was found similar in C. citiaris,jowal' kadbi, mixed grass and LLM and lower in urd bhoosa and GN haulm. In situ dry malter and crude protein disappearance for legume straws and L. leucocephala leaves were higher than those of non-leguminous forages. The trend of disappearance of dry matter was faster than crude protein in nonÂ· leguminous forages, however, in legume straws the disappearance of crude protein was faster than dry matter. While in L. leucocephala leaves the trend of disappearance of dry matter and crude protein was almost similar during 72 hr of incubation in rumen. The faster rate of disappearance of crude protein from leguminous forages DS compared to non. leguminous forages showed that legume proteins are readily available in the rumen and thus could be used as nitrogen supplement to improve the utilization orlow grade roughages.